2001
DOI: 10.1159/000053894
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Elevation of Maternal Serum Alpha-Fetoprotein Associated with Mosaic Trisomy 8 in a Liveborn

Abstract: Constitutional mosaic trisomy 8 has been associated with syndromic dysmorphology, corneal opacities, leukemias, and trophoblastic disease. However, abnormal maternal serum alpha-fetoprotein (MSAFP) has not been reported in association with mosaic trisomy 8. Our case first presented for evaluation of an extremely elevated MSAFP with mild elevation of MShCG in an otherwise normal pregnancy: MSAFP 13.89 MoM, MShCG 3.57 MoM, and MSuE3 1.04 MoM. Fetal dysmorphism was limited to bilateral pyelectasis and a prominent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Other features are cleft lip and/or palate, cardiac, renal, cerebral malformations, and mental retardation. Diverse chromosomal abnormalities have been associated with oculoauriculovertebral spectrum, such as trisomies of chromosomes 7, 8, 9, 10p, 22 [Hodes et al, 1981; Kobrynski et al, 1993; Pridjian et al, 1995; Miller et al, 2001; de Ravel et al, 2001; Dabir and Morrison, 2006], deletions in 1p22.2–p31.1, 5p14, 12p13.33, 18p, 22q11.2, 22qter [Buffoni et al, 1976; Herman et al, 1988; Derbent et al, 2003; Ala‐Mello et al, 2008; Callier et al, 2008; Xu et al, 2008; Digilio et al, 2009; Lafay‐Cousin et al, 2009; Rooryck et al, 2009], a duplication in 22q11q13 [Hathout et al, 1998], and unbalanced translocations including t(5;8)(p15.31;p23.1) [Josifova et al, 2004] and t(11;22)(q23;q11) [Balci et al, 2006]. Genetic linkage studies identified a locus in 14q32 containing the GSC (goosecoid) gene, but no mutation was found in this gene in patients with hemifacial microsomia [Kelberman et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Other features are cleft lip and/or palate, cardiac, renal, cerebral malformations, and mental retardation. Diverse chromosomal abnormalities have been associated with oculoauriculovertebral spectrum, such as trisomies of chromosomes 7, 8, 9, 10p, 22 [Hodes et al, 1981; Kobrynski et al, 1993; Pridjian et al, 1995; Miller et al, 2001; de Ravel et al, 2001; Dabir and Morrison, 2006], deletions in 1p22.2–p31.1, 5p14, 12p13.33, 18p, 22q11.2, 22qter [Buffoni et al, 1976; Herman et al, 1988; Derbent et al, 2003; Ala‐Mello et al, 2008; Callier et al, 2008; Xu et al, 2008; Digilio et al, 2009; Lafay‐Cousin et al, 2009; Rooryck et al, 2009], a duplication in 22q11q13 [Hathout et al, 1998], and unbalanced translocations including t(5;8)(p15.31;p23.1) [Josifova et al, 2004] and t(11;22)(q23;q11) [Balci et al, 2006]. Genetic linkage studies identified a locus in 14q32 containing the GSC (goosecoid) gene, but no mutation was found in this gene in patients with hemifacial microsomia [Kelberman et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…However, loss of the chromosome from the trisomic zygote derived from a normal gamete will produce an apparently normal diploid cell line with uniparental disomy [2]. Mosaicism for trisomy 8 has been diagnosed during the first trimester of pregnancy by detecting reverse end-diastolic ductus venosus flow [3] and during the second trimester by detecting an extreme elevation of maternal serum ·-fetoprotein [4]. Confined placental mosaicism for trisomy 14 and maternal uniparental isodisomy 14 in association with elevated second trimester maternal serum chorionic gonadotropin and Matheson/Matheson/McCorquodale/ Santolaya-Forgas third trimester fetal growth restriction has also been reported [5].…”
Section: Introductionmentioning
confidence: 99%